Comparing glueline characteristics and bonding durability between Sago Bark and Acacia mangium - Fathymah, Tukijo. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Wood is a useful material that always reacts with adhesive or glue to produce plywood or particleboard. They have several characteristics to be considering ensuring that the bonding between wood and adhesive is strong and durable. The objectives of this study were to determine the buffer capacity, to compare the wettability and contact angle, and the bonding strength of board made between sago bark and Acacia mangium. They were flaked, grounded and air-dried to moisture content of 12% to 14%. The buffer capacity of the sago bark and Acacia mangium were acidic at pH 5.81 and 5.75. Contact angle between sago bark and Acacia mangium board surface with water and urea formaldehyde adhesive showed the relationship between the wettability and bond strength, where the bond strength decreased as contact angle increased Particleboard properties for sago bark and Acacia mangium showed an internal bond, 0.37 N/mm2 and 0.43 N/mm2. The FTIR analysis indicated that bonding between sago bark with urea formaldehyde was quite similar to the bonding of Acacia mangium with urea formaldehyde. The conclusion drawn from this project is that sago bark has poorer glueline characteristics and showed the less durable bonding with urea formaldehyde as compare to Acacia mangium.